(untitled) (Swiss Medical Weekly, 2014)
OBJECTIVE: Coronary artery bypass grafting (CABG) using extracorporeal circulation (ECC) is still the gold standard. However, alternative techniques have been developed to avoid ECC and its potential adverse effects. These encompass minimal extracorporeal circulation (MECC) or off-pump coronary artery bypass grafting (OPCAB). However, the prevailing potential benefits when comparing MECC and OPCABG are not yet clearly established. METHODS: In this retrospective study we investigated the potential benefits of MECC and OPCABG in 697 patients undergoing CABG. Of these, 555 patients had been operated with MECC and 142 off-pump. The primary endpoint was Troponin T level as an indicator for myocardial damage. RESULTS: Study groups were not significantly different in general. However, patients undergoing OPCABG were significantly older (65.01 years ± 9.5 vs. 69.39 years ± 9.5; p value <0.001) with a higher Logistic EuroSCORE I (4.92% ± 6.5 vs. 5.88% ± 6.8; p value = 0.017). Operating off pump significantly reduced the need for intra-operative blood products (0.7% vs. 8.6%; p-value <0.001) and the length of stay in the intensive care unit (ICU) (2.04 days ± 2.63 vs. 2.76 days ± 2.79; p value <0.001). Regarding other blood values a significant difference could not be found in the adjusted calculations. The combined secondary endpoint, major cardiac or cerebrovascular events (MACCE), was equal in both groups as well. CONCLUSIONS: Coronary artery bypass grafting using MECC or OPCABG are two comparable techniques with advantages for OPCABG regarding the reduced need for intra-operative blood products and shorter length of stay in the ICU. However serological values and combined endpoint MACCE did not differ significantly in both groups.